ANALISIS SITIRAN SKRIPSI JURUSAN KEDOKTERAN UMUM TAHUN 2016 DAN KETERSEDIAANNYA DI PERPUSTAKAAN FAKULTAS KEDOKTERAN UNIVERSITAS JENDERAL SOEDIRMAN - Nurochman, Arif; Romadon, Romadon; Hariyadi, Ari; Kurniasih, Wuri; Kasworini, Endang (Direktorat Repositori, Multimedia, dan Penerbitan Ilmiah - Badan Riset dan Inovasi Nasional (BRIN Publishing), 2018)
Characteristics of user in academic library require speed and extent of information services. Librarian need to know which literatures that often read and available in the library. Citation analysis is used to find out what kind of citation most used by users and to know avaibility of library collection. This study aims to describe citation that used in thesis of Department General Medical of Medical Faculty, Jenderal Soedirman University in 2016. The purpose of this study is to determine the type of literatures that citated, to identify the language that citated, and to determine the literature avaibility that citated in Medical Faculty library. The research method using descriptive method by using data analysis of citation analysis on the list of thesis literature of Medical Faculty of Medicine students Jenderal Soedirman University in 2016. The Population is all thesis of Department of General Medical in 2016 that amounting 148 thesis. Data analysis based on percentage which is described by data tables. The results of the study obtained totaly 5315 citation and showed a variety of literature cited among other books 2601 citation (49%), journal 2261 citation (43%), internet sources 188 citation (3.5%), thesis 148 citation (2.7%), magazine 70 citation (1.3%), thesis 37 citation (0.6%), 7 citation proceedings (0.13%), 2 citation (0.03%), and 1 citation (0.01%) publication. The literature language often cited in English is 3468 citation (65%) versus 1847 (35%) Indonesian citation. While the available literature cited 3.91% available, versus 96.08% of the literature is not available.